The Development of the Module of Educational Semi-Comic Anti-Corruption Integrated in PPKN Learning for Junior High School Students - Ningsih, Wella Ayu; Rafni, Al; Dewi, Susi Fitria; Ofianto, Ofianto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The paper aims to develop an Integrated Anti-Corruption Education Comic Module and to find out the effectiveness of the semi-comic integrated anti-corruption education module in Civics learning for class VII students at SMPN 19 Kerinci. This type of research is Research and Development. The population in this study were all students of class VII at SMP Negeri 19 Kerinci. The sampling technique used is non-probability sampling with purposive sampling. The product will be validated by experts and tested on class VII students at SMP Negeri 19 Kerinci. Qualitative data were obtained through observation, written responses, and suggestions, while quantitative data were obtained from questionnaires and tests. The practicality of the module is determined based on the response of the teacher and students. Based on considerations consisting of three students who have high, medium, and low abilities (individual evaluation) and one class of students in class VII SMP Negeri 19 Kerinci (large scale trial). Data collection instruments consisted of observation sheets, questionnaire sheets, and question sheets. The results showed that the results of the validity of media experts were 93%, material experts 91%, and linguists 90%, with very valid categories. As for the practicality test, with an average of 91.5 in the very practical category. For effectiveness, the data source is obtained from the learning outcomes of students before and after using the semi-comic module. The pre-test results obtained an average of 46, and during the post-test, it increased to 94. The results of this research and development can conclude that the use of the module semi-comic anti-corruption education integrated into PPKN learning for class VII students at SMP Negeri 19 Kerinci is appropriate.